Total Anti-Oxidant Capacity of Saliva in Chronic Periodontitis Patients Before and After Periodontal Treatment - Shirzaiy, M; Ansari, S M; Dehghan, J H; Ghaeni, S H (Journal of Nepal Health Research Council, 2015)
Background: Periodontal disease is among the most common inflammatory conditions which is associated with many different factors. One of the contributing factors to the pathogenesis of this condition may compromise the defensive  mechanism of antioxidants. The present study evaluates the antioxidant capacity of saliva in periodontal patients beforeand after periodontal treatment.Methods: In this cross sectional study, 31 patients systemically healthy non smokers with chronic periodontitis were recruited. The antioxidant capacity of saliva was measured before the initial phase of periodontal therapy and after completion of the treatment. Data were analyzed using SPSS 19 software. Paired T-Test, Independent sample T-test  and ANOVA tests were used as appropriated.Results: The mean and standard deviation  antioxidant capacity of the saliva after the treatment.(0.962± 0.287µM) was significantly higher than before the treatment (0.655 ± 0.281 µM ,p<0.001). The mean difference of antioxidant capacity of the saliva before and after periodontal treatment was higher among men than among women; however,the difference was not significant (P=0.07). The mean difference of salivary antioxidant capacity was not significantly differed among different ages (P=0.772).Conclusions: The antioxidant capacity  of saliva was higher after periodontal therapy among patients with periodontal disease, however the change was not varied across the ages and gender. Therefore, the alterations in the defensive mechanism of antioxidants could be the key factors contribute to the pathogenesis of periodontal diseases. Keywords: antioxidants; periodontitis; saliva.